Phases and binding of reflexives and pronouns in English - Canac-Marquis, Réjean (Proceedings of the 12th International Conference on Head-Driven Phrase Structure Grammar, 2005)
This paper proposes a distinct approach to local binding effects for reflexivesand pronominals in English whereby the nature of local binding domains is aby-product of the incremental interpretation of syntactic derivations(Uriageraka 1999, Chomsky 2000, 2001), emphasizing the role of theConceptual /Intentional interface and the computational system (i.e. bareoutput conditions) in shaping general principles of grammars. A significantdevelopment of the Minimalist framework is the proposal that derivationsoperate through phases or multiple spell outs, which allows to reduce thestrict cyclicity of derivations, and related locality effects of movement, tointerface (bare output) conditions and economy conditions. In this paper Ipropose that incremental interpretation can further capture local bindingdomains effects of conditions A and B of Chomsky's (1981, 1986) BindingTheory. Basically, local binding domains are shown to correspond to<q>accessible phase domains</q>. Our proposal hence contrasts with standardanalyses (e.g. Reinhart and Reuland 1993, Pollard and Sag 1992) that defineco-argumenthood as the core factor from which binding conditions aredeveloped. Our proposal also provides a new perspective on the corecontrasts between A-chain and A-bar chain w.r.t. binding and scopereconstruction effects and argues that checking of the uninterpretable featureCase is what defines potential phase domains.